An inventory of reptiles and amphibians in North-west of SiberutIsland, West Sumatera - Irvan - Sidik (ZOO INDONESIA, 2008)
Sidik. I. 2008. An inventory of reptiles and amphibians in North-west of SiberutIsland, West Sumatera. Zoo Indonesia 17(2): 35-47. Siberut island is the largest landarea of the Mentawai Archipelagos, in West of the Sumatera Island. Its preservation isof the utmost important to the conservation of tropical forests island. The survey ofherpetofauna was conducted at the inland forest in North-west Siberut island. A totalof 73 specimens were collected consisted of 26 species of reptiles (5 species of agamids,4 species of geckos, 5 species of skinks, 1 species of varanid, 7 species of snakes, 2species of freshwater turtles & 2 species of marine turtles) and 11 species of amphibians(1 species of toad, 1 species of tree hole frog, 6 species of frogs, 1 species of puddlefrog & 2 species of tree frogs). Comparative results of these collections with previouspapers revealed that the existing data of herpetofauna in Siberut was probably atintermediate in number to Sumatera and Malay Peninsula species.